Importance of Participatory Process in Urban Regeneration: Case Study of Wat Mangkorn Kammalawat MRT Station’s Surrounding Areas - Kangwanpoom, Churit (Journal of Architectural/Planning Research and Studies (JARS), 2014)
The study project of the participatory process in urban regeneration around Wat Mangkorn Kammalawat MRT Station was initiated by landlords who were interested to develop their lands around the MRT Station, and was conducted by the representative from 2009 to 2010. Nevertheless, the project could not achieve the targets and was terminated. This research has objectives to determine the factors leading to the failure of the project, learn the flaw of the project running, and propose the ways to adjust the role of stakeholders and improve the working steps in urban regeneration. In 2011, I have summarized the knowledge from the project with local community and experts, listening to their comments and suggestions toward urban regeneration with participatory process. The results from the research found that all stakeholders need to adjust their roles. The landlords should be sincere to solve the problem and more involve with the project by participating in community meeting or being a part in the working team. Community should realize their importance toward district and should be united. Project researchers should set their position as the information provider and supporter only. The structure and working process of the project should be adjusted by including people from all sides, encouraging community to participate in problem solving, and conducting the public hearing when need to determine the conclusion in the future.